KOMPETENSI LITERASI DIGITAL SISWA DALAM PEMBELAJARAN DARING DI SMP NEGERI 2 KABANJAHE - Benediktus Benteng Kurniadi; Pranata Bukit; Melina Tamba; Elita Modesta Br Sembiring (Academy of Education Journal, 2023)
This study aims to describe the skills and abilities of students in using digital media and to find out the obstacles experienced by students as well as the efforts made by teachers in improving skills in online learning. This research uses desciptive qualitative method. It applies the observation, and interviews to get the data. The result shows that: the use of digital media in SMP Negeri 2 Kabanjahe includes the ability to connect in online learning, the ability to communicate in online learning and the ability to do and submit the assignments in online learning. Evaluation of information content includes a student's ability to think critically and provide an assessment of what is found online accompanied by the ability to identify the validity and completeness of information. Producing information content includes the ability to produce or create content such as Facebook, writing on a blog or website, create video clips using images or audio, or other forms of content.